APPLICATION OF DMAIC AND TAGUCHI METHODS TO MINIMIZE THE DEFECTIVE PRODUCTS FLIP LIGHTSPEED CLIPBAR - Yani Iriani; Putri Ferdina Aryanti; Faizal Rachman Saleh; Andar Tri Wahyudi; MuhammadHilmy Allam Albari (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
PT X is an industrial company that produces sandals including Lightspeed Clipbar, Lightspeed Clip sandals and Lightspeed Cross Bar sandals. The problem that occurs is that there is one sandal product with the highest level of disability, namely the Eiger Lightspeed Clipbar sandal product which reaches 9,101% per year. The purpose of this study was to identify the type of defect in the Lightspeed Clipbar sandal product through the DMAIC stages (Define, Measure, Analyze, Improve, and Control)) and make a proposed improvement in the assembling and buffing process at PT X. Based on the results of the study, identified factors causing defects between Other: open bonding, the sides of the sandals are not neat and the erosion of the Lightspeed Clip logo sandals. Factors that cause sandals are defects, glue, soles and benzene. The DPMO (Defect per Million Opportunities) value of the DMAIC results is 30376.12 with an average sigma score of 3.38. The sigma value does not meet the sigma process capability standards for industries in developed countries, which is 5-6 sigma. While the results of the Taguchi experimental calculations the value of the average quality characteristics for sandals defects amounted to 3.40 to 0.32 and the S / N quality characteristics of 10.67 to 0.24. The conclusion of this study resulted in corrective action on the Eiger Lightspeed Clipbar sandals product, which is obtained the optimal level setting of factors that affect the defects of Eiger Lightspeed Clipbar sandals, including the 28g glue factor, 15 mm rubber soles and 13 mm benzene. Confirmation results with an optimal setting level obtained values of 3.31 to 0.38, as well as S / N quality characteristics for the defects of the Lightspeed Clipbar sandals 10.54 to 0.